Galactosaemia: diagnosis, management and long-term outcome. Issue 3 (March 2015) - Broomfield, A.; Brain, C.; Grunewald, S.
Abstract: Classical galactosaemia (OMIM 230400) is an inherited disorder of galactose metabolism. The toxic potential of ingested galactose (derived predominantly from lactose) and build-up of intermediates was recognised over 100 years ago. The most common and most severe form is classical galactosaemia, resulting from galactose-1-phosphate uridyl transferase deficiency (GALT). In the UK, patients are usually diagnosed only after they become symptomatic – galactosaemia is not included in the newborn screening programme. Treatment is based on restriction of galactose in the diet, mainly by excluding lactose which is found in milk, milk products and manufactured foods containing milk. Early diagnosis is crucial to prevent acute life threatening complications. Long-term outcome in classical galactosaemia in the overall patients' population remains disappointing. This review gives a summary of current practises, updated recommendations and highlights potential disease burden.